SOCIAL NETWORKS AND ACCESS TO INVESTMENT CAPITAL AMONGST BLACK ENTREPRENEURS - FIHLA, ANDILE KENNETH LUVUYO (My University, 2011)
An analysis of the types of social networks amongst black entrepreneurs revealed the existence of both strategic networks of business associates and politics and organic networks of sport and family. However, social networks involving political connections and business associates were found to be dominant. The entrepreneurs cited the two main reasons for belonging to a social network as access to knowledge and information. The research investigated the nature of the relationship between social networks and access to investment capital amongst black entrepreneurs. This specifically related to whether social networks increase knowledge about sources of funding, whether they facilitated the flow of capital to black entrepreneurs and what were the implications of social networks for black entrepreneurs. Whilst all social networks played a role in referring black entrepreneurs to their funders, only the strategic networks of business associates and political actively influenced the last deals of black entrepreneurs. The role of social networks in influencing deals was found to be prevalent amongst women members of the network. Whilst the prior knowledge of the funders by the majority of the black entrepreneurs did not reduce the cost of funding, it implies that black entrepreneurs used existing contacts to access capital. This coupled with the finding that optimal length of service for accessing capital was five to ten years, suggests that new measures need to be found to improve access to funding for new black economic empowerment entrants.
MBA - WBS
Keywords: Social networks; Investment capital; Entrepreneurs, Black